STUDY OF ECO-ARCHITECTURE CONCEPT AT MARINA BAY SANDS HOTEL - Haykal, Muhammad; Lissimia, Finta (Jurnal Koridor, 2021)
Eco-architecture is a sustainable concept which in essence prioritizes natural and environmental aspects in an architectural design. In addition, eco-architecture also focuses on the use of natural energy as an alternative energy source to replace fossil energy which produces C02 which causes damage to natural ecosystems and causes harm to the living things in it. In this research, Marina Bay Sands Hotel is the object of hotel research that uses the concept of eco-architecture in its design. There is also a discussion on the building's energy operational system in which there are passive systems, hybrid systems, active systems and productive systems as levels in the use of building energy with the aim of providing efficient energy for buildings. The last is about the identification of harmony which includes discussing the configuration of the building mass and the orientation of the building. Based on the analysis carried out with the components previously mentioned, it can be concluded that the application of eco-architecture based on its principles has a significant impact on environmental conditions around the site. This is because these principles are principles that pay attention to environmental conditions during the construction period and after the building is active, which makes the building a sustainable building Â